Der Berater als Fremder: eine soziologische Studie zur Managementberatung in Universitäten - Krücken, Georg; Serrano-Velarde, Kathia (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2016)
The paper conceives consultants as organizational outsiders who enter the organization for a short period of time without being affected by the consequences of their action. In contrast to current organizational research that understands consultants as objective third or boundary-spanning innovators, we focus on the limits of consulting work: Is it possible to observe practices or idiosyncrasies that are non-negotiable for an organization and therefore resist the intervention of consultants? Our study is based on qualitative interviews we conducted at German, French and British universities that secured the services of management consulting firms. Conceptually, our analysis is based on the distinction between institutional and organizational identities. We marshaled insights from sociological systems theory and neo-institutional theory to question traditional concepts of organizational identity. By focusing on the conflicts that emerged in the framework of consulting projects at universities, we were able to go to the bottom of academic resistance to consulting work. Indeed, our analysis shows that the nature of knowledge produced in university settings and the deliberative communication culture belong to the institutionalized identity of universities and therefore systematically lead to conflicts and open resistance within consulting projects.